“El Procedimiento Especial de Desalojo con Intervención Notarial y Ejecución del Juez para garantizar el Derecho a la Seguridad Jurídica, Propiedad Privada y Celeridad Procesal” - Naula Maita, Pablo Alexander (2024)
This Curricular Integration Work focused on the legal, doctrinal and comparative study, to carry out a Special Eviction Procedure with Notarial Intervention and Enforcement of the Judge, to ensure the Right to Legal Security, Private Property and Procedural Speed, because to carry out an eviction process in Ecuador, when the tenant refuses to return the property due to termination of the lease or non-payment of the lease fee, the process is carried out in court, a process that has become complicated and prolonged due to the accumulated procedural burden in the courts, The process is carried out in the courts, a process that has become complicated and prolonged due to the procedural burden accumulated in the courts, having to be waiting for the proceedings to be dispatched and the process is delayed while waiting for it to be substantiated before a judge, so this research shows that there is a need for the Notary Law to empower the Notary with the power to solemnize the eviction in Article 18 of the powers of the Notary. In our Ecuadorian legislation this concept is new and nonexistent, for the reason that in the notarial activity there is no such power, but being a much more agile procedure would bring several advantages to our society as the decongestion of the specialized units of the Civil at the national level and not being regulated within our legal system its incorporation would be a great contribution to the resolution of disputes in the field of Tenancy.